The Relationship Between Internet Addiction and Body Mass Index in Turkish Adolescents - (:unkn) unknown (MARY ANN LIEBERT, INC, 2014)
The purpose of this study was to investigate Internet use patterns and Internet addiction among adolescents and to examine the correlation between Internet addiction and eating attitudes and body mass index (BMI). The study was conducted among 1,938 students, aged between 14 and 18 years. The Internet Addiction Test (IAT), the Eating Attitudes Test (EAT), and a sociodemographic query form were used to collect data. According to the IAT, 12.4% of the study sample met the criteria for Internet addiction. A significant positive correlation between BMI and the IAT (r=0.307; p<0.01) and weekly Internet use (r=0.215; p<0.01) was found. Nine students with Internet addiction (3.8%) and 90 with average Internet use (5.3%) were found to have a possible eating disorder (p>0.05). No relationship was found between the EAT and the IAT and duration of weekly Internet use. Linear regression analysis revealed a significant independent association of the IAT with BMI (r=0.235; p<0.001). These results indicate an association between Internet addiction and BMI. Further studies are needed to describe the causality of this association.
Keywords: PSYCHIATRIC COMORBIDITY; OBESITY; OVERWEIGHT; PREVALENCE; COMPUTER; CHILDREN; ASSOCIATION; DISORDERS; CHILDHOOD; SYMPTOMS